1995
DOI: 10.1016/0022-5096(94)00060-i
|View full text |Cite
|
Sign up to set email alerts
|

Origin of crack tip instabilities

Abstract: This paper demonstrates that rapid fracture of ideal brittle lattices naturally involves phenomena long seen in experiment, but which have been hard to understand from a continuum point of view. These idealized models do not mimic realistic microstructure, but can be solved exactly and understood completely. First it is shown that constant velocity crack solutions do not exist at all for a range of velocities starting at zero and ranging up to about one quarter of the shear wave speed. Next it is shown that ab… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

13
247
0

Year Published

1996
1996
2017
2017

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 283 publications
(260 citation statements)
references
References 37 publications
13
247
0
Order By: Relevance
“…In addition, it is necessary to prescribe that the displacement of nodes ahead of the transition front remain below this critical displacement [Marder & Gross (1995)]. This admissibility criterion is violated when the feeding wave amplitude (at a given frequency) is high enough.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, it is necessary to prescribe that the displacement of nodes ahead of the transition front remain below this critical displacement [Marder & Gross (1995)]. This admissibility criterion is violated when the feeding wave amplitude (at a given frequency) is high enough.…”
Section: Discussionmentioning
confidence: 99%
“…The radiation creates the speed-dependent wave resistance, which cannot be detected in a homogeneous material model, [Slepyan (2002), Slepyan (2010a)]. This phenomena accounts for instabilities in the crack path propagation in a homogeneous material, which is attributed to the composition of its microstructure, [Marder & Gross (1995)], that can yield complex crack behaviour such as micro-branching and oscillation of the crack paths [Bouchbinder et al (2010)]. …”
Section: Introductionmentioning
confidence: 99%
“…The effective sharpness of the blade depends upon the power with which it presses through material; press too hard, and it blunts, presenting enormous resistance to speeding up further. Both idealized calculations [3,4], as well as more realistic simulations [5,6] showed how this process could occur, as indicated on the right hand side of Fig. . Last fall, Sharon, Fineberg, and Gross [7] showed that cracks in Plexiglas develop branching structures, as shown on the right hand side of Fig. .…”
mentioning
confidence: 99%
“…Thus, a better understanding of fracture mechanisms in solids is obviously of crucial importance for a safer design of civil engineering structures. A large number of studies-both experimental and theoretical-have been devoted to the simplest model case of a single crack, growing in either brittle or viscoplastic materials [1][2][3][4][5][6][7][8]. Those works have shown that dynamical instabilities and/or heterogeneities may destabilize the crack dynamics, leading to strong deviations and roughness in the crack paths [6][7][8][9][10][11][12].…”
mentioning
confidence: 99%